Economic Challenges for East Timor - Mats Lundahl; Fredrik Sjöholm (Lund University, School of Economics and Management, Department of Economics, 2020)
The situation in East Timor is turbulent and future growth prospects are indeterminate. This paper discusses the economic challenges facing East Timor. Most inhabitants depend on subsistence farming and there is a need to both modernize agriculture and to foster a modern sector that can generate employment for the growing population. Public expenditures play an important role in this development and East Timor is fortunate to have a large petroleum fund to utilize for economic growth and development. Unfortunately, the fund is about to dry up. There are also clear signs that a large part of investments and development efforts are misplaced. Political conflicts and weak institutions are explaining some of the failures to generate a more growth enhancing economic environment.
Keywords: O13; O14; O53; 330; East Timor; Development; Oil; Agriculture; Industr